Visual Outcomes from Shunting for Idiopathic Intracranial Hypertension. (December 2014) - Hickman, S. J.; Raoof, N.; Panesar, H.; McMullan, J. M.; Pepper, I. M.; Sharrack, B.
ABSTRACT A retrospective notes review was conducted for 50 consecutive patients who underwent shunt surgery for idiopathic intracranial hypertension (IIH). The decimal visual acuity and the mean radial degrees (MRD) of the I4e isopter of the Goldmann visual field were measured pre-operatively and after a mean follow-up period of 1123 days (range: 13–3551 days). A ventriculo-peritoneal shunt was the first procedure in 38 patients and a lumbo-peritoneal shunt in 12. The mean decimal visual acuity of the worse affected eye improved from 0.75 to 0.84, p = 0.011. The MRD score of the worse affected eye improved on average from 25.6° to 35.5°, p < 0.0001. In those with significant pre-operative visual impairment in their worse affected eye (defined as an MRD score ≤30°), the MRD score improved on average from 10.3° to 26.5°, p = 0.0008. The mean number of surgical procedures for each patient was 2.8 (range: 1–15). Taking all surgical procedures into account, post-operative complications were experienced by 30 patients. At last follow-up, 28 patients still complained of headache, 8 of whom had the intervention performed primarily for headache. Shunting can improve visual function in patients with IIH. There is significant post-operative morbidity and often the need for repeated procedures. Headache also commonly remains in these patients. There is a need for a randomised controlled trial of operative interventions in IIH. Sample size calculations for such a trial to treat significant vision loss are presented.